Analisis Forensik Database Menggunakan Metode Forensik Statis - Riadi, Imam; Umar, Rusdy; Bernadisman, Dora (JSINBIS (Jurnal Sistem Informasi Bisnis), 2019)
SIMDA (Regional Management Information System) is a system created by the BPKP (Financial and Development Supervisory Agency) to assist local governments in implementing regional financial management so that it complies with applicable, efficient, effective, transparent, accountable and auditable regulations. Management data is stored in the SIMDA database on a server connected to a computer network, it is possible that the database is always infiltrated and indicated by data manipulation by hackers. The purpose of this study is to monitor database activity and detect data manipulation done by hackers, then forensic processes are carried out using static forensic methods with stages, namely data collection, data checking, data analysis, and reporting so as to provide evidence and instructions to do analysis on the SIMDA Planning database. The results obtained using static forensic methods show that there has been manipulation or change in the budget ceiling of the activity that exceeds the program budget ceiling (mark-up in budget planning) carried out by hackers who enter through the SIMDA database. Output from forensic processes can prove manipulation data that is carried out by hackers can be detected using SQL Profiler and SQL Log Analyzer tools so that output can be used as digital evidence to assist law enforcement in revealing cybercrime crime cases and can be accounted for in court proceedings.